Cladistic analysis of Abracrini genera (Orthoptera, Acrididae, Ommatolampinae) - Da Costa, Maria Kátia Matiotti [UNESP]; Carvalho, Gervásio Silva; Fontanetti, Carmem Silvia [UNESP] (Magnolia Press, 2010)
A cladistic analysis using 50 characters and 21 genera of the Neotropical tribe Abracrini was performed in order to test the monophyly of the tribe and to reconstruct a phylogenetic hypothesis. Abracrini is supported by three synapomorphies: penultimate article of maxillary palps unflattened; second segment of hind tarsi short and internal apophysis of cerci vestigial. The analysis demonstrates that Abracrini is a monophyletic tribe, as well as a relationship among its genera was (Psiloscirtus splendidus (((Parasitalces sexnotata + Sitalces volxemi) (Arimacris trinitatis (Caruaruacris bivittatus + Salvadoracris nigritus))) (((Eusitalces vittatus + Liebermannacris dorsualis) (Monneacris fascipes (Robustusacris balzapambae (Xiphiola borellii (Eujivarus fusiformis + Roppacris griseipes))))) (((Omalotettix obliquus + Orthoscapheus coryaceus) (Abracris dilecta + Jodacris ferruginea)) (Teinophaus saussurei (Rhachicreagra nothra (Agesander ruficornis + Ixalotettix compactus))))))). Further data on biogeography and a distribution map are provided. Copyright © 2010 Magnolia Press.
Keywords: distribution; grasshoppers; Neotropical region; phylogeny; taxonomy